“Outside Agencies Do Not Bring Development”: Mennonite Central Committee and the Decades-Long Challenge of Decolonizing Aid - Epp Weaver, Alain; Smith Cain, Emma (Christian Relief, Development, and Advocacy: The Journal of the Accord Network, 2023)
Contemporary calls to “decolonize aid” have historical roots. In this article, the authors focus on Mennonite Central Committee (MCC) as a case study of how one Christian humanitarian, development, and peacebuilding agency has grappled for at least five decades with how to carry out its mission in a way that abdicates colonial power and fosters mutually transformative partnerships with churches and other organizations in the Global South. Exploring how MCC has thought about the power it wields offers insights and lessons for other international aid agencies, both Christian and non-Christian, about the complexities and opportunities involved in attempts to decolonize aid. External and internal pressures to show impact, demonstrate relevance, and ensure compliance with standardized policies and procedures have all generated tensions within MCC’s efforts to decolonize its work: other international aid agencies, the authors suggest, will encounter similar tensions as they work at decolonizing aid.